Implementasi Pendidikan Inklusif Di Sekolah Dasar Negeri Pecarikan - Khulasoh Himawati; Fikria Najitama; Maryanto Maryanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine how the implementation of inclusive education at SDN Pecarikan Kebumen. This study uses descriptive qualitative research methods. Data collection is done by using the method of observation, interviews, and documentation. The data collected in the form of planning, implementation, and evaluation of the implementation of inclusive education consisting of educators and principals of SDN Pecarikan Kebumen. Data analysis techniques used with data reduction, data presentation and drawing conclusions. The results of the study it can be concluded that the implementation of inclusive education at SD Negeri Pecarikan uses the planning, implementation, and evaluation stages. The planning stage includes the preparation process, the preparation of work programs and the management structure at SD Negeri Pecarikan Kebumen. Then, at the implementation stage of implementing inclusive education at SD Negeri Pecarikan Kebumen, it is carried out according to the condition of the existing resources at the school. At the evaluation stage, it is carried out once a year which is held at the annual meeting which is attended all teacher staff and employees SD Negeri Percarikan.